Stages of Using Ward and Peppard Methods in Information System Strategic Planning - Anggy Giri Prawiyogi; Aang Solahudin Anwar (ADI Publisher, 2021)
In an organization, there are three main targets for the application of information systems and information techniques that will be applied. In the information management process, automation is needed. This will help work efficiency. It is necessary to fulfill the need for information that will be used in decision making in management to increase effectiveness. There needs to be a change in the style and way of doing business in the company in order to increase competitiveness with competing companies. The goals or goals of a company and strategies in IT will enable us to achieve the 3 targets above, therefore it is necessary to have the right organizational business strategy that leads to the company's goals, as well as support that comes from designing IT infrastructure that is in accordance with the organization's business strategy in IT strategy.An understanding of the organization's business strategy needs to be mastered in order to be able to develop an appropriate IT strategy so that it can be a supporter of achieving the company's vision and mission. The ward and peppard methodologies will be used in the explanation of the following IT/IS strategic planning stages.